Advertisement and courtship calls of Phyllodytes wuchereri (Peters, 1873) (Anura: Hylidae) - Cruz, Deise; Marciano-Jr, Euvaldo; Napoli, Marcelo Felgueiras (Zootaxa, 2014)
The genus Phyllodytes Wagler comprises 11 species, of which six have vocalizations already described [P. edelmoi Peixoto, Caramaschi & Freire, 2003 (Lima et al. 2008); P. gyrinaethes Peixoto, Caramaschi & Freire, 2003 (Roberto & Ávila 2013); P. luteolus (Wied-Neuwied, 1824) (Weygoldt 1981); P. melanomystax Caramaschi, Silva & Britto-Pereira, 1992 (Nunes et al. 2007); P. kautskyi Peixoto & Cruz, 1988 (Simon & Peres 2012); and P. tuberculosus Bokermann, 1966 (Juncá et al. 2012)]. Here we describe the advertisement and courtship calls of P. wuchereri (Peters, 1873) recorded at the Private Reserve of Natural Heritage (RPPN) Serra Bonita, in the Camacan municipality, Bahia State, Brazil (15o23′S, 39o33′W; 900 m a.s.l.). This is the first description of a courtship call of the genus Phyllodytes.